2010
DOI: 10.1159/000319893
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Functional Polymorphism in the MMP-3 Gene with Moyamoya Disease in the Chinese Han Population

Abstract: Background: Moyamoya disease (MMD) is an uncommon cerebrovascular disease characterized by progressive stenosis of the intracranial internal carotid arteries and their proximal branches. The important role of genetic factors in the etiology and pathogenesis of MMD is being increasingly recognized. The study was designed to examine the association of single nucleotide polymorphisms in matrix metalloproteinase (MMP) and tissue inhibitors of metalloproteinase (TIMP) genes with MMD occurrence. Methods: A case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…These findings support the view that a genetic factor may play a role in the incidence of MMD. [23][24] It is well-known that MMD occurs mostly in children in Asia. 13 However, the present study showed a preponderance of adults.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the view that a genetic factor may play a role in the incidence of MMD. [23][24] It is well-known that MMD occurs mostly in children in Asia. 13 However, the present study showed a preponderance of adults.…”
Section: Discussionmentioning
confidence: 99%
“…Tortuosity of cerebral arteries has been reported for aged, hypertensive patients [5,23,24,69] and in patients with ‘Moyamoya’ disease [70,71,72]. Cerebral arteries may also become tortuous due to malformation [73] or increased flow [34,35] associated with elastin degradation.…”
Section: Etiology: Association With Vessel Diseases and Clinical Consmentioning
confidence: 99%
“…though authors of recent genetic studies have made efforts to identify several candidate loci (chromosomes 3p24-26, 6q25, 8q23, 12p12, and 17q25 4,6,24,31 ) and several susceptibility genes (ACTA2, RPTOR, PDGFRB, MMP3, and TGFB1 2,3,15,16 ) related to MMD, the RING (Really Interesting New Gene) finger protein 213 gene (RNF213) is the only susceptibility gene for MMD identified by both genome-wide association studies and exome sequencing.…”
mentioning
confidence: 99%